Non-invasive, non-enzymatic, non-serodiagnostic, and home-detecting paper-based “abnormal UA alarm” for early diagnosis of UA associated diseases - Qian Zhang; Hui’e Jiang; Zhijian Li; Lijuan Chen; Fengqian Yang; Jiamin Zhang; Bo Zhang; Xinhua Liu (Journal of Bioresources and Bioproducts)
Uric acid (UA) level is a pivotal clinical human-health biomarker providing predictive feedback for multitudinous well-known kidney, cardiovascular and metabolic syndrome diseases. Off-the-shelf UA detection methods clinically rely on uricase suffer from limitations such as high costs, longstanding result acquisition, circumscribed testing locations, rigorous expertise requirements, and difficulty in home-detecting due to serum testing systems. Here, inspired by the pH-paper, a scaleable, rapid, non-invasive/-enzymatic/-serodiagnostic, and home-detecting “abnormal UA alarm” platform for UA detection in saliva was developed by strategically integrating the proposed paper-based fluorescent sensing-materials (NIFP-SM) with a user-orientated intelligent red-green-blue (RGB) analysis device. Therefore, NIFP-SM is nano-engineered through straightforward interfacial interactions of functional building blocks of on-demand naphthyl imide-derived fluorescent self-assembled micro-particles (NIFS) with lamellar structure and commercially-used filter paper. The NIFS possesses dominantly wide detection range (0–5 000 µmol/L) and high sensitivity (limit of detection = 0.91 µmol/L). Surprisingly, NIFS exhibited outstanding identifiability for uric acid even in the presence of 34 interferents, substantiating accurate detection-capability in intricate environments. Thus NIFP-SM equipped with NIFS resoundingly achieved efficient, rapid, and on-site visual detection of UA in saliva, urine-simulants, and foods. Further, the NIFP-SM-based automatic analysis platform integrated with an intelligent RGB analysis device was manufactured and enabled accurate quantitative, low-cost, non-invasive/-enzymatic/-serodiagnostic, rapid, home-detecting for UA, eliminating the need for costly equipment and specialized personnel and thereby facilitating early-warning detection of abnormal UA-levels associated diseases.